# calculus

posted by .

Solve the equation:

Cos^2x + cosx + 0

• calculus - info -

no equation

If you mean cos^2x + cosx = 0 then we have

cosx(cosx+1)=0
cosx = 0 or -1
x = pi/2 or pi or 3pi/2

## Respond to this Question

 First Name School Subject Your Answer

## Similar Questions

1. ### Trig

prove the identity (sinX)^6 +(cosX)^6= 1 - 3(sinX)^2 (cosX)^2 sinX^6= sinx^2 ^3 = (1-cosX^2)^3 = (1-2CosX^2 + cos^4) (1-cosX^2) then multiply that out 1-2CosX^2 + cos^4 - cosX^2 + 2cos^4 -cos^6 add that on the left to the cos^6, and …
2. ### Pre-Calc

Trigonometric Identities Prove: (tanx + secx -1)/(tanx - secx + 1)= tanx + secx My work so far: (sinx/cosx + 1/cosx + cosx/cosx)/(sinx/cos x - 1/cosx + cosx/cosx)= tanx + cosx (just working on the left side) ((sinx + 1 - cosx)/cosx)/((sinx …
3. ### pre-calc

Solve: cos(2x-180) - sin(x-90)=0 my work: cos2xcos180 + sin2xsin180= sinxcos90 - sin90cosx -cos2x - sin2x= cosx -cos^2x + sin^2x -2sinxcosx=cosx I'm stuck here. I tried subtracting cosx from both sides and making sin^2x into 1- cos^2x, …
4. ### Maths

Solve this equation fo rx in the interval 0<=x<=360 3sinxtanx=8 I would do it this way: sinxtanx = 8/3 sinx(sinx/cosx)=8/3 sin^2x/cosx = 8/3 (1-cos^2x)/cosx=8/3 cross-multiply 3 - 3cos^2x = 8cosx 3cos^2x + 8cosx - 3 = 0 (3cosx-1)(cosx+3)=0 …
5. ### Trigonometry.

( tanx/1-cotx )+ (cotx/1-tanx)= (1+secxcscx) Good one! Generally these are done by changing everything to sines and cosines, unless you see some obvious identities. Also generally, it is best to start with the more complicated side …
6. ### Calculus

How would I find the antiderivative of this equation?
7. ### RESPONSE to PreCalc Question

h t t p : / / w w w . j i s k h a . c o m / d i s p l a y . c g i ?
8. ### Calculus 2 Trigonometric Substitution

I'm working this problem: ∫ [1-tan^2 (x)] / [sec^2 (x)] dx ∫(1/secx)-[(sin^2x/cos^2x)/(1/cosx) ∫cosx-sinx(sinx/cosx) ∫cosx-∫sin^2(x)/cosx sinx-∫(1-cos^2(x))/cosx sinx-∫(1/cosx)-cosx sinx-∫secx-∫cosx …
9. ### Math

Suppose f(x) = sin(pi*cosx) On any interval where the inverse function y = f –1(x) exists, the derivative of f –1(x) with respect to x is: a)-1/(cos(pi*cosx)), where x and y are related by the equation (satisfy the equation) x=sin(pi*cosy) …
10. ### Pre-calculus

Prove the following identities. 1. 1+cosx/1-cosx = secx + 1/secx -1 2. (tanx + cotx)^2=sec^2x csc^2x 3. cos(x+y) cos(x-y)= cos^2x - sin^2y

More Similar Questions